2021
DOI: 10.24191/ijsms.v6i1.12875
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Knowledge and Practice Towards Prevention of Surgical Site Infection

Abstract: Surgical Site Infection (SIS) is a common healthcare-associated infection that significantly impacts patient safety and financial losses for health systems. Enhancing nurses' knowledge and practice is an essential component in the prevention of the spread of infection. The study aims to assess the knowledge and practice of preventing surgical site infection among nurses. A cross-sectional study was conducted among 306 nurses in two public hospitals in Malaysia. Data were obtained from selfadministered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…these results agreed with the study of Sham (11)who reported that the number of married nurses (83.7%) was more than the number of unmarried. Also, a study done by Novelia (12) found that the majority of the participants (71.1%) were married.…”
Section: Discussionsupporting
confidence: 93%
“…these results agreed with the study of Sham (11)who reported that the number of married nurses (83.7%) was more than the number of unmarried. Also, a study done by Novelia (12) found that the majority of the participants (71.1%) were married.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this study further highlight challenges such as inadequate supervision and difficulties in developing and maintaining spousal relationships. Adequate supervision is important for quality healthcare delivery by building the competence of nurses ( Bellerose et al, 2021 ; Buchan et al, 2013 ; Sham et al, 2021 ) but this was generally lacking among many of the nurses in the study area, leading to a feeling of isolation and neglect. Minimal supervision from health authorities has led to healthcare workers concluding that their superiors/bosses do not regard their well-beings as a priority ( Chapman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%